Răspuns:
Explicație pas cu pas:
[tex]\frac{10}{6}[/tex]
i)
a) [tex]\frac{10}{6} = \frac{10*3}{6*3} = \frac{30}{18} = \frac{5}{3}[/tex]
b) [tex]\frac{10}{6} = \frac{10*3}{6*3} = \frac{30}{18} = \frac{5}{3}[/tex]
c) [tex]\frac{10}{6} = \frac{10*0.6}{6*0.6} = \frac{6}{3.6}[/tex]
ii)
a) [tex]\frac{10}{6} = \frac{10:2}{6:2} = \frac{5}{3}[/tex]
b) [tex]\frac{10}{6} = \frac{10:0.2}{6:0.2} = \frac{50}{30} = \frac{5}{3}[/tex]
c) [tex]\frac{10}{6} = \frac{10:0.4}{6:0.4} = \frac{25}{15} = \frac{5}{3}[/tex]